2021
DOI: 10.3389/fnins.2021.632312
|View full text |Cite
|
Sign up to set email alerts
|

Western Diet Consumption During Development: Setting the Stage for Neurocognitive Dysfunction

Abstract: The dietary pattern in industrialized countries has changed substantially over the past century due to technological advances in agriculture, food processing, storage, marketing, and distribution practices. The availability of highly palatable, calorically dense foods that are shelf-stable has facilitated a food environment where overconsumption of foods that have a high percentage of calories derived from fat (particularly saturated fat) and sugar is extremely common in modern Westernized societies. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 206 publications
(215 reference statements)
2
45
1
1
Order By: Relevance
“…Given that increased anxiety-like behavior may develop following early life WD exposure in rodents (Tsan et al, 2021), we tested the rats in the Zero Maze test but found no effects of CAF exposure on anxiety-like behavior either before or after the dietary intervention. Similar to our CAF rats, an anxiety-like phenotype was not seen in the SUG cohorts, which is consistent with our previous findings in male rats using the Zero Maze test (Hsu et al, 2015b;Noble et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that increased anxiety-like behavior may develop following early life WD exposure in rodents (Tsan et al, 2021), we tested the rats in the Zero Maze test but found no effects of CAF exposure on anxiety-like behavior either before or after the dietary intervention. Similar to our CAF rats, an anxiety-like phenotype was not seen in the SUG cohorts, which is consistent with our previous findings in male rats using the Zero Maze test (Hsu et al, 2015b;Noble et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to adverse metabolic outcomes, WD exposure during early life periods of development adversely impacts neurocognitive development (Francis and Stevenson, 2013;Noble and Kanoski, 2016;Reichelt, 2016;Tsan et al, 2021). For example, habitual added sugar consumption in children is associated with altered hippocampus (HPC) volume and HPC-cortical connectivity (Clark et al, 2020), whereas habitual saturated fatty acid intake is negatively associated with HPC-dependent relational memory (Baym et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…During the last decades, the sugar intake has been markedly increased ( 40 ). The higher luminal sugar concentrations, the more upregulation of the enzymatic and absorptive systems, with higher glucose absorption consequently ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…The dramatic increase of nutrients and beverages which are enriched with sucrose has led to higher amount of fructose in the food ( 40 ). In humans, the capacity of fructose absorption is much smaller than the glucose absorption ( 41 ).…”
Section: Gastrointestinal Effects Of Monosaccharide Absorptionmentioning
confidence: 99%
“…In addition to adverse metabolic outcomes, WD exposure during early life periods of development adversely impacts neurocognitive development [8][9][10][11]. For example, habitual added sugar consumption in children is associated with altered hippocampus (HPC) volume and HPC-cortical connectivity [12], whereas habitual saturated fatty acid intake is negatively associated with HPC-dependent relational memory [13].…”
Section: Introductionmentioning
confidence: 99%